The Effects of Teaching Reading Explicitly to Students with a Learning Disability in Reading - Meghan L., Jenson (My University, 2014)
Students with a Specific Learning Disability (SLD) in reading are not closing the skill gap and substantially increasing their reading ability before leaving high school. This study will examine the effect of explicit instruction in fluency, comprehension, phonemic awareness, vocabulary, and phonics on high school students with a SLD in reading over the course of nine academic school weeks. Eight of ten invited students participated with parental consent. Weekly Data based on weekly reading assessments was gathered and interpreted to determine the effects of explicit reading instruction and if it produces growth. The findings of this study support that explicit reading instruction is beneficial for students with a SLD in reading, however prolonged instruction is the key to success.
Keywords: high school; Specific Learning Disability; reading; SLD; phonemic awareness; vocabulary; fluency; comprehension; phonics